PNA- and SBA-positive lymphocytes content in the major salivary glands’ structures during early postnatal period after intrauterine antigenic action - І. N. Maslova (Patologìâ)
Aim – to determine the Peanut agglutinin- and Soybean agglutinin-positive (PNA+, SBA+) lymphocytes content in the major salivary glands’ structures in early postnatal period after intrauterine antigenic action.